Bulgaria : Accounting and Auditing - World Bank (Washington DC, 2013)
An assessment of accounting and auditing practices in Bulgaria is a part of the World Bank and the International Monetary Fund (IMF) joint initiative on reports on the Observance of Standards and Codes (ROSC). The assessment focused on the strengths and weaknesses of the accounting and auditing environment that influences the quality of corporate financial reporting. It used the International Accounting Standards (IAS) and the International Standards of Auditing (ISA) as benchmarks. It involved a review of both mandatory requirements and actual practices. The report has found that the transition to full IAS compliance will be demanding. It requires extensive education in a different style and philosophy of accounting requirements. The transition is made all the more difficult by the decision to require all entities to comply with IAS. This is a much greater burden than applies in any EU Member State. Finally, the transition to full IAS may face considerable push back from regulators who fail to differentiate between general purpose and regulatory financial statements. There is currently no effective enforcement of compliance with national accounting standards and there are conflicting opinions about the effectiveness of the audit quality control reviews carried out by the Institute of Certified Public Accountants of Bulgaria (ICPAB). This report draws upon recent international experience in developed economies and recommends that the current self-regulation of the audit profession should be reviewed and an adequate oversight mechanism established.